Reforming European Universities and Reforming European Welfare States: Parallel Drivers of Change? - Kwiek, Marek (My University, 2013)
We are discussing here links between reform agendas and their rationales in higher education and in the welfare state. Lessons learnt from welfare state reforms can be useful in understanding higher education reforms, and we see the links between the two under-‐researched. Assuming that higher education services have traditionally been state-‐funded welfare state services in postwar Continental Europe, welfare state reforms debates as a background to higher education reforms debates are a significant missing link. We intend to fill this gap and explore possible links between the two largely isolated policy and research areas. Permanent processes of reforming universities in the last two or three decades do not lead to their complete reform. They rather lead to further, ever deeper, reforms across Europe. As Jürgen Enders and colleagues put it recently, “nowhere today is higher education undergoing more substantial change than in Europe”. The whole idea of the welfare state is under renegotiations, and the conditions for access to, and eligibility, for various tax-‐based public services are under discussions. It is increasingly related to possible individual contributions (co-‐funding and private policies in healthcare, multi-‐pillar schemes in pensions, and cost-‐sharing in higher education). Transforming governments have been following in the last two decades the rules of a zero-‐sum game: higher expenditures in one sector of public services or public programs (pensions or higher education) occurred at the expense of expenditures in other sectors of public services (healthcare), programs or public infrastructure (roads, railroads, law and order etc.). The financial dimension of changes in both welfare state and higher education seems crucial, especially that costs generated by all welfare state components and each of them separately cannot be easily reduced.
Keywords: higher education reforms; university reforms; welfare state; welfare state reforms; reforms; public sector; European universities; European welfare states; globalization; Europeanization; drivers of change; institutional change; public services; neoliberalism; market forces; postnational constellation; risk society; modernity; comparative higher education; comparative welfare state; comparative research; Central Europe; governance models; welfare state models; welfare typology; non-core no-state; marketization; commodification; external revenues; cost-sharing; pension systems; European welfare model; European social model; welfare restructuring; economic pressures; ideology; austerity; economic crisis; public services; cost-benefit